The Role of Contextual Factors in Private Sector Engagement: A Case Study of Private Sector Contribution to COVID-19 Mitigation in Nigeria - Okeke, Chinyere; Eigbiremolen, Godstime O.; Uzochukwu, Benjamin; Mbachu, Chinyere; Onwujekwe, Obinna (Frontiers in Public Health, 2022)
The Private Sector Coalition against COVID-19 (CACOVID) was established on the 27th of March 2020 to mobilize private sector resources toward supporting the government's response to the COVID-19 pandemic. More specifically, CACOVID set out to provide leadership functions, raise public awareness, provide buy-in for COVID-19 prevention, and provide direct support to strengthen the health system's capacity to respond to the crisis. In this paper, we examine the contextual factors that shaped the private sector's engagement in the fight against the pandemic with a view to identifying progress and learning opportunities. A desk review of the existing literature and documents from relevant stakeholders (government, organized private sector, and civil society organizations) was carried out. Using both the Grindle and Thomas (1) and Husted and Salazar (2) frameworks, we identified individual characteristics (industry expertise and position, philanthropy, and personal/economic interest); the economic crises created by the pandemic; a weak health system; and the multi-sectoral nature of the response to the pandemic.as contextual factors that influenced public-private collaboration in tackling the COVID-19 pandemic in Nigeria. That is, the private sector collaborated with the government based on several interrelated contexts that confront them with issues they need to address; determine what options are feasible politically, economically, and administratively; set limits on what solutions are eventually considered; and respond to efforts to alter existing policies and institutional practices. The identified contextual factors provide learning opportunities for enhancing public-private partnership in advancing healthcare not just in Nigeria, but also in related countries in Africa and other developing countries.